The Role of Attachment Styles and Emotion Regulation in Future Thinking of Children - Aghabalazadeh Koljahi, Leila; Rafezi, Zohreh (Mental Health and Lifestyle Journal, 2026)
Future thinking is one of the fundamental cognitive abilities that plays a crucial role in children’s adaptive functioning and future success. Therefore, examining the factors involved in its development and enhancement is essential. The present study aimed to investigate the role of attachment styles and emotion regulation in the development of future thinking among children aged 6 to 12 years. This research employed a causal-comparative design, and the statistical population consisted of all children within the 6–12 age range and their parents. A total of 85 children were selected through convenience sampling and then based on their future thinking scores were assigned to two groups with high- and low-level of future thinking (31 participants in each group). Data were collected using standardized questionnaires, including the Future Thinking Questionnaire (Mazachowsky & Mahy, 2020), the Emotion Regulation Checklist (Shields et al., 1997), and the Attachment Style Questionnaire (Finzi-Dottan et al., 2000). Descriptive and inferential statistics were applied to analyze the data. The findings revealed that, in the high future thinking group, scores of emotion regulation, secure and avoidant attachment styles were significantly higher (P < 0.05). Conversely, in the low future thinking group, emotional lability or negativity was significantly higher (P < 0.05). No significant difference was observed between the two groups regarding ambivalent attachment style (P > 0.05). Overall, the results indicated that secure and avoidant attachment styles, as well as emotion regulation ability, play a significant role in the development of children’s future thinking, and emphasizing the importance of attachment-based interventions and strengthening emotional regulation for enhancing children’s future thinking.